The Art of Baksa Dance: Tradition and Education in Trusmi Village - Sulistyami, Ibtisamah Hidayatullah; Sinaga, Syahrul Syah; Hartono, Hartono (Universitas Negeri Medan, 2024)
The researcher conducted research at Sanggar Gending Nada Bersemi on how Baksa dance is learned and its relevance for studio members in the preservation of Baksa dance at the Memayu ceremony in Trusmi Village, Plered District, Cirebon Regency. This research uses qualitative methods. The data collection procedures used in this research are observation, interviews, and documentation techniques. The steps for the selection process of the first baksa dance is the announcement of the traditional memayu ceremony of Trusmi village. The second step is the announcement of the selection of Baksa dancers, the third step is the first training to learn the basic movements of Baksa dance, then the trainer will select all dancers by assessing how the wiraganya is the accuracy of movement or the arrangement of movements when dancing Baksa dance. if the Baksa dancer selection participants are more than 40 people then in the first week elimination is carried out. the process of selecting Baksa dance dancers is carried out 14 days before the memayu traditional ceremony. Selection is carried out from the screening stage, selecting from basic movements, positioning, to performing pilgrimage activities. In learning Baksa dance, demonstration and contextual learning methods are used. Because baksa dance is a traditional ceremonial dance, the demonstration method is the most appropriate method because each movement has provisions and cannot be changed.